Sarawak Energy Berhad / Alphonsus Obbermann Anchang - Anchang, Alphonsus Obbermann (University Technology MARA Sarawak, 2017)
Sarawak Energy Berhad is both an energy development company and a vertically integrated electricity utility with a vision to achieve sustainable growth and prosperity for Sarawak by meeting the regional’s need for reliable, renewable energy. With a multidisciplinary workforce comprising about 4500 employees, Sarawak Energy serve more than 630,000 customers across the State. Building on a strong foundation nearly 100 years as an effective utility company, Sarawak Energy is taking bold steps to support the transformation of Sarawak in its division to become a develop state by the year 2030. In line with their broader roles and responsibilities, Sarawak Energy has embarked on a massive transformation journey since 2010, to advance from a traditional utility company into modem and agile corporation.